Microbiological characteristics of palm oil mill effluent - Kar, Ming Tan (2015)
The term "wastewater fingerprint" portrays all activities in a particular industry are registered and reflected in its wastewater. Studies on wastewater give very detailed picture on the processes involved in a particular industry. World major agro-industrial effluents have received attention on its characteristics, treatment processes, and more recently on its recovery or reuse. For the palm oil mill effluent (POME), concerted research activities have been accentuating on its treatment via various high-end processes as well as reclaiming the effluent for industrial use. On its characteristics, the constituents present such as the biodegradable organic materials, nutrients, inorganic fractions, metals, thermal effects in addition to the odour were well studied. Though, the microbiology aspect is overlooked. The diverse microbial communities are known to play a crucial role in the degradation of POME. Hence, the study of microbiological characteristics lays a foundation to promote a greater performance of wastewater treatment. Better understanding on the roles of the microorganisms involved in POME degradation, could assist in achieving higher removal efficiency. This included studies on the phenol-removing bacteria, nitrification and denitrification bacteria, sulphur-producing and hydrogen-producing bacteria, as well as other bacteria responsible for organic and colour removal from the POME. In this paper, the microorganisms from POME (bacteria, algae, and fungi) and their roles in treatment processes are reviewed. This will provide an insight of microbiological characteristics of POME so as to lay a foundation to combining microbiological and physiochemical aspects in wastewater treatment in order to enhance removal efficiency.